Tears of Rage : The Racial Interface of Modern American Fiction-Faulkner, Wright, Pynchon, Morrison - Brivic, Sheldon, 1943- (Book collections on Project MUSE., 2008)
In this provocative study, Shelly Brivic presents the history of the twentieth-century American novel as a continuous narrative dialogue between white and black voices. Exploring four of the most renowned and challenging works written between 1930 and 1990-William Faulkner's Absalom, Absalom!, Richard Wright's Native Son, Thomas Pynchon's V., and Toni Morrison's Beloved-Brivic traces how these works progress through the interaction of white and black perspectives toward confronting the calamity of slavery and its reverberating aftermath and continuing legacy. Brivic shows how one novel leads i.